PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI 002 JUMRAH KECAMATAN RIMBA MELINTANG - Harahap, Siti Hapsah; Marhadi, Hendri; Noviana, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Internal issue Background this research is student less comprehend the items of Mathematics Iesson. This Matter is seen from still lower the nya flatten - flatten the result learn the Mathematics namely 57,00 as well as still lower the nya of attainment KKM namely, from 20 student only 5 student or 25% a success reach the KKM. As for KKM specified by a school is 70. Problem of this research is